2005
DOI: 10.1007/s00606-004-0258-4
|View full text |Cite
|
Sign up to set email alerts
|

Floral and pollinator behaviour of flexistylous Bornean ginger, Alpinia nieuwenhuizii (Zingiberaceae)

Abstract: Flexistyly is a unique floral mechanism involving extreme curving of the style. It was first described in Chinese ginger (Amomum, Zingiberaceae). This is a pioneer report on flexistylous gingers of Malesia, where most species of this family grow. We observed the floral behaviour and flower visitors in Alpinia nieuwenhuizii Val., a Bornean endemic.Although the floral behaviour and effective pollinators (carpenter bees, Xylocopa) were similar between the Bornean species and the previously reported flexistylous A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Unlike heterostyly and enantiostyly, this polymorphism does not involve pollen segregation on pollinators' bodies to achieve intermorph pollination. Remarkably, the stylar movements of the morphs tend to be synchronous and correlated with the foraging behaviour of floral visitors, mostly large-bodied bees, particularly Xylocopa (Zhang et al 2003;Takano et al 2005). The floral morphs in flexistylous populations are reported to occur in equal frequencies but extensive surveys have yet to be undertaken and the inheritance of the polymorphism is unknown.…”
Section: Phylogenetic Evidence Indicates Evolutionary Transitionsmentioning
confidence: 99%
“…Unlike heterostyly and enantiostyly, this polymorphism does not involve pollen segregation on pollinators' bodies to achieve intermorph pollination. Remarkably, the stylar movements of the morphs tend to be synchronous and correlated with the foraging behaviour of floral visitors, mostly large-bodied bees, particularly Xylocopa (Zhang et al 2003;Takano et al 2005). The floral morphs in flexistylous populations are reported to occur in equal frequencies but extensive surveys have yet to be undertaken and the inheritance of the polymorphism is unknown.…”
Section: Phylogenetic Evidence Indicates Evolutionary Transitionsmentioning
confidence: 99%
“…and later reported in Alpinia (Takano et al. ) in Borneo. We did not observe any movement of the style in Scaphochlamys but this mechanism has been observed in two‐day flowering Boesenbergia (Ooi pers.…”
Section: Discussionmentioning
confidence: 73%
“…Another study in Borneo reported carpenter bee pollination of Alpinia nieuwenhuizii Valeton (Takano et al. , ).…”
Section: Introductionmentioning
confidence: 99%
“…Takano et al. () mentioned the differences of visiting pattern of pollinators between subtropics and tropics. In subtropics, the peak of flower visit is around noon.…”
Section: Discussionmentioning
confidence: 99%
“…), Alpinia nieuwenhuizii (Takano et al. ), Etlingera yunnanensis (Kress et al. ), Plagiostachys strobilifera (Takano et al.…”
Section: Introductionmentioning
confidence: 99%